Stratigraphy and Habitation Features at DIA.4(JfE1-4), a Dorset Site in Arctic Quebec - Badgley, Ian (ARCTIC, 1980)
The 1978 Tuvaaluk Programme excavation at DIA.4 (JfE-4) revealed evidence of 15 habitation features in a stratified context. These features, comprising both semi-subterranean dwellings and tent emplacements, are summarized and stratigraphically organized into chronologically successive occupation phases at the site. Excavation results suggest certain methodological implications of importance to the interpretation of the Dorset settlement pattern in Ungava.